Simultaneous enantioselective analysis of illicit drugs in wastewater and surface water by chiral LC–MS/MS: A pilot study on a wastewater treatment plant and its receiving river. (15th March 2021) - Wang, Weimin; Guo, Changsheng; Chen, Like; Qiu, Ziwen; Yin, Xingxing; Xu, Jian
Abstract : An enantioselective method for quantifying amphetamine-type chiral illicit drugs (CIDs) in wastewater and surface water was developed, validated, and applied to samples from a wastewater treatment plant (WWTP) and its effluent-receiving river in Beijing, China. Water samples were subjected to solid-phase extraction (SPE) and then quantified via liquid chromatography–tandem mass spectrometry. The enantioseparation of CIDs was performed with a CHIRALPAK CBH column. Chromatographic parameters, including mobile phase composition and flow rates, were tested to identify the satisfactory enantiomeric resolution. The SPE method was optimized by evaluating variables, including SPE cartridge types, extraction solvents, and solvent volumes. The Oasis HLB sorbent showed good performance with recoveries exceeding 60% and matrix effects ranging from −19.6% to 26.6% for most target enantiomers, except for norephedrine (NE), in three different aquatic matrixes. The established method was superior to previously reported methods and had a low limit of detection, low limit of quantification, and short runtime (<45 min). The repeatability and reproducibility of the method reached 19.1% and 17.8%, respectively. The method was successfully utilized to monitor the daily variations in CIDs in the influent, effluent, and effluent-receiving river of a WWTP in Beijing over 1 week. The common occurrence of 1 R, 2 S-(−)-ephedrine (1 R, 2 S-(−)-EPH), 1 S, 2 S-(+)-pseudoephedrine (1 S, 2 S-(+)-PEPH), R-(−)-methamphetamine (METH), and S-(+)-METH in wastewater samples was observed. Ephedrines (1 R, 2 S-(−)-EPH and 1 S, 2 S-(+)-PEPH) were the most abundant CIDs in the influent, effluent, upstream, and downstream samples with concentrations of 725.8 ± 181.2 ng/L, 22.9 ± 4.9 ng/L, 12.96 ± 0.79 ng/L, and 11.6 ± 6.7 ng/L, respectively. METH was detectable in most water samples and was present in excess in S-enantiomer form in the influent and in R-enantiomer form in the effluent and surface water. R-(−)-MDMA was detected at a concentration of up to 2.4 ng/L in the influent. The metabolites norketamine (NK), amphetamine(AMP), MDA, and NE were not detected in water samples given the low concentration of their parent drugs. Graphical abstract: Image 1 Highlights: A method for quantifying chiral drugs in water samples was developed and validated. The method was successfully employed to analyze chiral illicit drugs in a WWTP in Beijing. R-(−)-MDMA was for the first time reported in the influent in Beijing, China.